A PHASE I-II FEASIBILITY TRIAL OF CANCER CARER MEDICINES MANAGEMENT: AN OVERVIEW. (1st March 2013) - Latter, S; Hopkinson, J; Richardson, A; Lowson, E; Duke, S; Anstey, S; Bennett, M; Smith, P; May, C
Abstract : Introduction: Seventy-onepercent of people with cancer experience pain at the end of life (Teunissen et al 2007). It is well established that family carers play a significant role in managing pain medication. Our scoping exercise of international literature repeatedly found that family carers lack information and confidence, with some holding beliefs that pain cannot be controlled and concerns about medication becoming addictive. Carers' roles have been neglected, with few interventions concerning pain management focusing specifically on carers, and a particular lack of UK research. Aims and Methods: A Phase I-II feasibility study, funded by Dimbleby Marie Curie, is being conducted (2013–2015) to develop a new Cancer Carer Medicines Management intervention and to test its feasibility, acceptability and efficacy to improve carers' knowledge, beliefs, skills and self-efficacy for pain medicines management, decrease carer strain and improve mood state. This will be achieved through: a rapid appraisal of research on interventions for carer management of end of life pain medicines; development and refinement of the intervention through user collaboration; and a feasibility trial involving nurses and carers in two sites, to inform a follow-on randomised control trial. Results: Phase I will produce an educational intervention for delivery by palliative care nurses with family carers. Phase II will evaluate intervention impact on carer outcomes using validated questionnaires measuring carer pain medication knowledge, beliefs and skills; carer strain, self-efficacy and mood state. Secondary outcomes from validated questionnaires and interviews will include perceptions of patient pain, burden of the intervention, and factors inhibiting or facilitating intervention use.